Comprehensive Review of Advanced Techniques in Cosmetic and Restorative Dentistry - Muslim, Sarah Talal Mohammed; Al Mazrouei, Raed Hamid; Al-Barakati, Alhassan Nayef; Al-Mutairi, Fahd Sagheer; Al-Khamisi, Faisal Ali; Surrati, Dr. Ahmed Wafa; Al solami, Amal Thiab; Dawaji, Sareh Hassan (Journal of Ecohumanism, 2024)
Aesthetic and reconstructive dental treatment has changed not only within the last two decades due to improvements in materials, technologies, and methods. Within this review, the author discusses the major contemporary developments in aesthetic and reconstructive treatments and techniques: New materials, minimally invasive approaches, digital technologies, and patient-centered treatment planning. The review also examines how these advancements enhance patient satisfaction, health, and survival. Also, problem areas and prospects of cosmetic and restorative dentistry are considered, particularly cost and accessibility barriers and customer demand changes.